Efecto de la manzanilla sobre el flujo y PH de la saliva. - Idrobo Paredes, Julia Stefanía (2016)
Quantitative, descriptive, transversal cut study to measured the effects of Chamomile in the salivary fluid and its PH. For the study, 70 Odontology students of the National University of Loja, the subjets of study were 26 men and 44 women, for the data recolection, the pH measurement and salivary fluid for 5 minutes (after ingesting an aidic drink/coffee and after ingesting chamomile tea) registered in the pertinent files of study. For data analysis the Chi- Square Test System Statistics IBM SPSS version 24 and descriptive statistical test was used. Increased fluid salival after intake of chamomile (0,21ml/min to 0,29ml/min) compared to basal salival fluid is evidenced; in case to salival pH there was a reestablishment in the neutral state (7,0) similar to the basal after to having checked decreased by ingesting coffee where the salival pH was 6,49. Regarding to the pH state after taking coffee, the salival pH descended in a 6,49. In statistical test could show that there is no relationship between the pH (p = 0.605) and fluid salival (p = 0.547) with gender. It is concluded that the consumption of natural chamomile infusion increases fluid salival and maintains the pH in the neutral state. Key Words: INFUSION, SALIVA, SIALOMETRY.